New records of feather mites (Sarcoptiformes: Proctophyllodidae) on tanagers (Passeriformes: Thraupidae) from Brazil - Hernandes, Fabio A. (Entomological Communications, 2021)
Herein, three feather mite species (Analgoidea: Proctophyllodidae) are reported from tanagers (Passeriformes: Thraupidae) in Brazil: Proctophyllodes thraupis Atyeo & Braasch, 1966 on Thraupis ornata (Sparrman, 1789), Thraupis palmarum (Wied, 1821), and Stilpnia peruviana (Desmarest, 1806); Amerodectes thraupicola (Černý, 1974) and Amerodectes bilineatus (Berla, 1958) on T. ornata. Proctophyllodes thraupis is herein reported for the first time on the hosts mentioned above. Amerodectes thraupicola is reported in synoxenism with A. bilineatus on the same bird specimen of T. ornata, a new host for both mites. Despite being described from a Cardinalidae (Passeriformes) host, this latter mite species was subsequently recovered only from tanagers, which reinforces the suggestion that non-thraupid hosts might be accidental records.